Expression of the short chain fatty acid receptor GPR41/FFAR3 in autonomic and somatic sensory ganglia - Nøhr, Mark Klitgaard; Gille, Andreas (Neuroscience, 2015)
G-protein-coupled receptor 41 (GPR41) also called free fatty acid receptor 3 (FFAR3) is a Gαi-coupled receptor activated by short-chain fatty acids (SCFAs) mainly produced from dietary complex carbohydrate fibers in the large intestine as products of fermentation by microbiota. FFAR3 is expressed in enteroendocrine cells, but has recently also been shown to be present in sympathetic neurons of the superior cervical ganglion. The aim of this study was to investigate whether the FFAR3 is present in other autonomic and sensory ganglia possibly influencing gut physiology. Cryostat sections were cut of autonomic and sensory ganglia of a transgenic reporter mouse expressing the monomeric red fluorescent protein (mRFP) gene under the control of the FFAR3 promoter. Control for specific expression was also done by immunohistochemistry with an antibody against the reporter protein. mRFP expression was as expected found not only in neurons of the superior cervical ganglion, but also in sympathetic ganglia of the thoracic and lumbar sympathetic trunk. Further, neurons in prevertebral ganglia expressed the mRFP reporter. FFAR3-mRFP-expressing neurons were also present in both autonomic and sensory ganglia such as the vagal ganglion, the spinal dorsal root ganglion and the trigeminal ganglion. No expression was observed in the brain or spinal cord. By use of radioactive-labeled antisense DNA probes, mRNA encoding the FFAR3 was found to be present in cells of the same ganglia. Further, the expression of the FFAR3 in the ganglia of the transgenic mice was confirmed by immunohistochemistry using an antibody directed against the receptor protein, and double labeling colocalized mRFP and the FFAR3-protein in the same neurons. Finally, quantitative real-time polymerase chain reaction (qRT-PCR) on extracts from the ganglia supported the presence mRNA encoding the FFAR3 in most of the investigated tissues. These data indicate that FFAR3 is expressed on postganglionic sympathetic and sensory neurons in both the autonomic and somatic peripheral nervous system and that SCFAs act not only through the enteroendocrine system but also directly by modifying physiological reflexes integrating the peripheral nervous system and the gastro-intestinal tract.
Gesehen am 19.12.2018